1-[(7E)-7-(2-Chlorobenzylidene)-3-(2-chlorophenyl)-3,3a,4,5,6,7-hexahydro-2H-indazol-2-yl]ethanone - Farook Adam (IUCrData, 2016)
In the title compound, C22H20Cl2N2O, the diazole ring adopts a shallow envelope conformation with the methine C atom bonded to the adjacent chlorobenzene ring as the flap. The dihedral angles between the heterocyclic ring and the pendant chlorobenzene rings are 61.4 (2) and 80.3 (2)°. In the crystal, weak C—H...Cl interactions connect the molecules into [001] chains.